Characterizing the design and economics components of jewellery into designomics model of indigenous community: a case study of Hmong Mae-Sa, Chiang Mai, Thailand / Jaruwan Pengsiri ... [et al.] - Pengsiri, Jaruwan; Boonsue, Worasiri; Hashim, Hema Zulaika; Hassan, Zakiyah (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2023)
This study aimed at (1) exploring the characteristics of Hmong silver jewllery and its production process and (2) proposing a new formula of design concerning design and economics components. The eight silver jewellery experts from the Hmong indigenous group were purposively selected as the participants. The in-depth interview was conducted to collect data about the entrepreneurship, the designomics and design process, and the knowledge management of the Hmong indigenous group. The results showed that (1) the main characteristics of Hmong's silver jewellery represented the natural environment, geometric shapes, implementation of modern patterns to original patterns and the production process consisted of five steps, and (2) a new formula concerning design and economics components consisted of three main components: Aesthetic component concerning the structure, pattern, and materials; Economic component concerning uniqueness, target customers, raw materials, setting a sale price, and sales distribution; and social responded component concerning community consideration, environmental consideration, and wisdom transfer to the next generation. The findings of this study advance our understanding on the interrelationship among wisdom, designs, and economics of Hmong's silver jewellery. They can be used as a guideline in silver jewellery production process contributing to jewellery business, especially that of the Hmong indigenous group.